(NnEZABYWAEMYE IMENA (B:s (No^ERKI O PIANISTAH(B-(NARMQNAH (B/s - d; (N{AGOQN(B, (Ng(B.(Nk(B.s ((NeREWAN (B:s (NiZD(B-(NWO egk(B,s, 2008)
(NrEZ@ME(B: (NARM(B., (NANGL(B.s
(NsWETLOJ PAMQTI MOEGO OTCA aRUT@NA oGANESOWI^A aPOQNAs
(NuKAZATELI(B: (NS(B. 210-225s
(NbIBLIOGR W PODSTRO^(B. (NPRIME^(B.s
Keywords: (NfORTEPIANNOE ISKUSSTWOs -- (NpIANISTY(B-(NARMQNEs; (NaRMQNSKIE MUZYKANTYs -- (NpIANISTYs